Implementing Question-Answer Relationship Strategy on Student's Reading Comprehension - Nurdiana, Nurdiana; Afrizal, Afrizal; Sutrisna, Sela; Fachrurrozi, Fachrurrozi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to evaluate students' reading comprehension, both taught and untaught, as well as the significant impact of the QAR strategy on students' comprehension. This study is categorized as quasi-experimental. For this study, the sample was collected through an easy sample approach. Eighth grade students at SMP Negeri 23 Pekanbaru were involved in this study in the academic year 2023-2024. The researchers analyzed the data using SPSS version 24. They used eta squared calculation and independent sample T-test. The results showed that there was a significant difference between students who were taught with the QAR strategy and students who were not, with the experimental class gaining 75.7% and the control class gaining 62.1%. Based on the eta square results, the researcher found that it was 0.054, which indicates a small influence. H0 is rejected, and Ha is accepted.